2012
DOI: 10.1073/pnas.1212806109
|View full text |Cite
|
Sign up to set email alerts
|

Blocking antibody to the β-subunit of FSH prevents bone loss by inhibiting bone resorption and stimulating bone synthesis

Abstract: Low estrogen levels undoubtedly underlie menopausal bone thinning. However, rapid and profuse bone loss begins 3 y before the last menstrual period, when serum estrogen is relatively normal. We have shown that the pituitary hormone FSH, the levels of which are high during late perimenopause, directly stimulates bone resorption by osteoclasts. Here, we generated and characterized a polyclonal antibody to a 13-amino-acid-long peptide sequence within the receptor-binding domain of the FSH β-subunit. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
143
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(166 citation statements)
references
References 39 publications
15
143
0
Order By: Relevance
“…1D. Dynamic histomorphometry was performed as described (53). The threepoint bending test was carried out according to a previous protocol (54).…”
Section: Methodsmentioning
confidence: 99%
“…1D. Dynamic histomorphometry was performed as described (53). The threepoint bending test was carried out according to a previous protocol (54).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, bone marrow stromal cells from FSHR -/-mice showed significantly greater colony-forming (Cfu-f) potential, suggesting a profound increase in osteoblastogenesis in the absence of the FSHR. Importantly, antibody injections did not affect serum estrogen levels in wild type mice [35]. Collectively, our studies provide clear evidence that lowering FSH in a hypogonadal state prevents bone loss.…”
Section: Fsh Antibody Rescues Hypogonadal Bone Lossmentioning
confidence: 55%
“…We found that this antibody not only attenuated osteoclastogenesis induced by FSH in vitro, but also prevented the loss of bone post-ovariectomy [35,36]. Most importantly, we noted through a detailed histomorphometric analysis that while bone resorption was reduced, bone formation was surprisingly elevated significantly [35].…”
Section: Fsh Antibody Rescues Hypogonadal Bone Lossmentioning
confidence: 71%
See 1 more Smart Citation
“…By modeling the Fshr-Fsh interaction in mouse, we developed a polyclonal antibody to a 13-amino acid sequence in the binding domain of Fshβ (12,15,16).…”
Section: Introductionmentioning
confidence: 99%